2015
DOI: 10.1002/pc.23394
|View full text |Cite
|
Sign up to set email alerts
|

Micro‐Driving behavior of carbon‐fiber‐reinforced epoxy resin for standing‐wave ultrasonic motor

Abstract: The application of the friction drive of carbon-fiberreinforced composites to a standing-wave ultrasonic motor was investigated. Friction drive tests were conducted on carbon-fiber-reinforced epoxy resins (CF/ epoxy) by home-made test rig, which was based on plate-rod vibrator. The effects of fiber orientation and ply thickness on dynamic drive and dynamic normal forces were investigated. Fiber orientation angle and ply thickness affected friction drive. Different dynamic drive forces, which varied both in amp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…f ( x ) is the geometric factor, defined as fx=6x1/2[]1.99goodbreak−x()1goodbreak−x()2.15goodbreak−3.93xgoodbreak+2.7x21+2x()1goodbreak−x3/2 where x = a/W and a is the initial notch length including the pre‐crack. The mode‐1 critical strain energy release rate is defined as G1c=1v2K1c2E where E is the elastic modulus acquired from the tensile test and v is the Poisson ratio of the epoxy, which is taken to be 0.34 46 …”
Section: Characterizationsmentioning
confidence: 99%
“…f ( x ) is the geometric factor, defined as fx=6x1/2[]1.99goodbreak−x()1goodbreak−x()2.15goodbreak−3.93xgoodbreak+2.7x21+2x()1goodbreak−x3/2 where x = a/W and a is the initial notch length including the pre‐crack. The mode‐1 critical strain energy release rate is defined as G1c=1v2K1c2E where E is the elastic modulus acquired from the tensile test and v is the Poisson ratio of the epoxy, which is taken to be 0.34 46 …”
Section: Characterizationsmentioning
confidence: 99%
“…Concurrently, Ishii et al [7] presented a method to predict the service life of USMs that use carbon fiber reinforced polymer as frictional materials, which was verified by the experiment. Subsequently, Lv et al [8][9][10][11][12][13][14] researched a series of polymer-based frictional materials, such as polytetrafluoroethylene (PTFE), phenolic resin, and Ekonol composites, and compared their tribological properties under different conditions to provide guidance for selecting frictional materials according to the operating condition. Wang et al [15,16] systematically studied the effect of fillers, topography, temperature, and vacuum on the wear behavior of PTFE composites and found that filling some functional additives could improve the wear resistance of the PTFE matrix.…”
Section: Introductionmentioning
confidence: 99%
“…Some frictional materials have been tested for USMs, including rubber, resin, metal coatings, alloys, and ceramic composites. It was found that most of them cannot meet the requirements due to, eg, severe wear, short service life, and high noise.…”
Section: Introductionmentioning
confidence: 99%
“…Ishii et al established a method to predict the service life of USMs with a carbon‐fiber‐reinforced polymer as the frictional material. Qu et al investigated the tribological properties of polytetrafluoroethylene (PTFE), phenolic resin, and Ekonol composites in different environments and proposed a method for selecting frictional materials incorporating operation conditions. Ding et al designed polyvinylidene fluoride and potassium titanate whisker reinforced polytetrafluoroethylene (PTW/PTFE) composites and found that such composites could improve the wear performance of USMs.…”
Section: Introductionmentioning
confidence: 99%